Evaluation of Rapid Chromatographic Immunoassay with Latex Agglutination Test and (ELISA) for Diagnosis of Human Toxoplasmosis - Hassan, jabbar S.; Ghazi, Haider f.; Ahmed, Abid Al-Razaq H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: there are different procedures for the diagnosis of females suspected with toxoplasmosis. However, time, cost, and accuracy of the test should meet patient’s needs. Material and methods: one hundred and eleven female with suspected toxoplasmosis were under go three different procedures for the diagnosis of Toxoplasma gondii infection. Latex agglutination test, rapid chromatographic (immunoblot) and ELISA test were done for all patients. The results were described as frequency and percentage of positivity; also, specificity and sensitivity of immunoblot were assessed according to the result of other tests. Results: The Latex test has shown 80% and 61.54% sensitivity and specificity respectively with IgG measured by ELISA while it has shown 100% sensitivity and specificity with IgM measured by ELISA. IgM immunoblot give a relatively higher sensitivity and specificity (95% and 98.89%) respectively than IgG immunoblot (88% and 89.29%) made with IgM and IgG ELISA respectively. Conclusion: Rapid chromatographic test considered as a good test for detection of IgG and IgM anti Toxoplasma gondii antibodies in both acute and chronic Toxoplasmosis.